Skrining Awal Toleransi Galur-galur Dihaploid Padi Gogo terhadap Cekaman Kekeringan pada Stadia Bibit - Kartina, Nita; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Wirnas, Desta; Nindita, dan Anggi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Development of doubled haploid lines of upland rice through anther culture is one way to obtain superior upland rice varieties tolerant to drought. The objectives of this research were to determine the response of doubled haploid lines to drought stress at seedling stage and to select tolerant doubled haploid lines. The research was conducted at a screenhouse of Muara Research Station, Indonesia Center of Rice Research (ICRR) from November to December 2017. Fourteen doubled haploid lines and 4 check varieties, namely Inpago 10 and Limboto, Salumpikit (drought tolerant check) and IR 20 (drought sensitive check) were used in this study. The experiment was arranged in a randomized complete block design with three replications. The observations were conducted on leaf rolling, leaf drought, and recovery ability. Based on Friedman nonparametric analysis, HR-5-7-1-1 and HR-7-15-2-1 had moderate response with estimated median values for leaf rolling of 3.44 and 3.00, respectively. Three doubled haploid lines namely HR-2-27-2-7, HR-2-34-1-3 and HR-7-15-2-1 had moderate response to drought with estimated median value of leaf drought of 3.56. Nine lines of doubled haploid had tolerant response with estimated median value of recovery ability of 1.00-1.56. Based on weighted selection index, nine doubled haploid lines with positive and high selection index were identified; however, only two lines (HR-7-15-2-1 and B3-2) had selection index higher than Inpago 10 and Limboto.Keywords: drought tolerance, leaf rolling, recovery, weighted selection index